A Meloidogyne incognita effector MiISE5 suppresses programmed cell death to promote parasitism in host plant - Qianqian Shi (Nature Portfolio, 2018)
Abstract Root-knot nematodes (RKNs) are highly specialized parasites that interact with their host plants using a range of strategies. The esophageal glands are the main places where nematodes synthesize effector proteins, which play central roles in successful invasion. The Meloidogyne incognita effector MiISE5 is exclusively expressed within the subventral esophageal cells and is upregulated during early parasitic stages. In this study, we show that MiISE5 can be secreted to barley cells through infectious hyphae of Magnaporthe oryzae. Transgenic Arabidopsis plants expressing MiISE5 became significantly more susceptible to M. incognita. Inversely, the tobacco rattle virus (TRV)-mediated silence of MiISE5 decreased nematode parasitism. Moreover, transient expression of MiISE5 suppressed cell death caused by Burkholderia glumae in Nicotiana benthamiana. Based on transcriptome analysis of MiISE5 transgenic sample and the wild-type (WT) sample, we obtained 261 DEGs, and the results of GO and KEGG enrichment analysis indicate that MiISE5 can interfere with various metabolic and signaling pathways, especially the JA signaling pathway, to facilitate nematode parasitism. Results from the present study suggest that MiISE5 plays an important role during the early stages of parasitism and provides evidence to decipher the molecular mechanisms underlying the manipulation of host immune defense responses by M. incognita.